Physico-chemical and technological properties of acai residue flour and its use (Research, Society and Development, 2021)
There are countless residues generated by the food industries, which leads to the search for alternatives for the use and development of by-products. Açaí residues, in turn, popularly known as 'sludge', are obtained in large quantities, in view of the amount processed in agro-industries. The present work aimed to study the physico-chemical and technological properties of açaí residue flour (FRA), and to evaluate its use, as an ingredient, in the processing of kibbeh. The following physical-chemical analyzes were carried out: moisture, proteins, lipids, ash, carbohydrates, energy value, fibers, pH and acidity. The technological properties studied were: water solubility, water absorption index and oil absorption index. For sensory evaluation, three kibbeh formulations were developed, with different concentrations of FRA (05, 10 and 15%). The FRA presented high levels of fibers and high caloric value, as well as satisfactory technological properties to use it, as an ingredient, in formulations of meat products. Kibbeh formulations with 05 and 10%FRA were preferred by consumers, making their addition a viable alternative for the food industries.